Branding only works on cattle : the new way to get known (and drive your competitors crazy) - Baskin, Jonathan Salem (New York : Business Plus, 2008)
A marketing maverick provides prescriptive advice on how to thrive in a world where pretty pictures and funny tag lines no longer lead to profits
Your branding is useless -- Traces in a cloud chamber -- The new Nike -- The rise of the anti-brand -- The myth of the consumer/producer -- The outsourcing of consent -- Games as purpose, not distraction -- It takes a company -- The buzz in buzz marketing -- The emperor's new clothes
Includes bibliographical references (p. 243-252) and index
Keywords: Branding (Marketing); Consumer behavior; Information behavior; Internet searching; Business enterprises -- Computer network resources